2014
DOI: 10.1186/1471-2458-14-678
|View full text |Cite
|
Sign up to set email alerts
|

Negative life events and migraine: a cross-sectional analysis of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) baseline data

Abstract: BackgroundStress is a typical migraine trigger. However, the impact of negative life events on migraine activity is poorly studied. The aim of this study is to investigate the association between negative life events and migraine using data from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) baseline assessment.MethodsELSA-Brasil is a multicenter cohort study conducted in six Brazilian cities. Baseline assessment included validated questionnaires for headache classification and the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
7
0
1
Order By: Relevance
“…Participants who reported experiencing headache in the last 12 months at baseline were invited to answer a detailed headache questionnaire based on the International Headache Society criteria (IHS‐2013), adapted for the Brazilian Portuguese language. This questionnaire has been validated and used previously in Brazil [Santos et al, ,]. The questionnaire investigates pain frequency, duration, quality, location, intensity, and triggering, as well as accompanying symptoms, such as nausea or vomiting [Santos et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants who reported experiencing headache in the last 12 months at baseline were invited to answer a detailed headache questionnaire based on the International Headache Society criteria (IHS‐2013), adapted for the Brazilian Portuguese language. This questionnaire has been validated and used previously in Brazil [Santos et al, ,]. The questionnaire investigates pain frequency, duration, quality, location, intensity, and triggering, as well as accompanying symptoms, such as nausea or vomiting [Santos et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…The Frequent Headache Epidemiology Study suggested that patients with CM had more major life events in the year preceding the chronification of their migraines than did patients with EM 31. The Longitudinal Brazilian study (ELSA-Brasil) showed an association between negative life events and increased frequency of migraine 32. Stress management with relaxation therapies, biofeedback and cognitive behavioural therapies were proven to be effective migraine prophylaxis measures 33–37…”
Section: Psychiatric Comorbidities Associated With Migrainementioning
confidence: 99%
“…Globally, migraine is also associated with variable but substantial negative personal impacts on education, career, and finances . A cross‐sectional study conducted in multiple headache centers in Austria demonstrated that approximately 34% of respondents, most of whom had episodic (56.4%) or chronic headache (38.3%), reported that their headaches had a negative impact on their careers and 21.5% reported a negative impact on earnings.…”
Section: Introductionmentioning
confidence: 99%